Exploring Teacher’s Attitude Toward Students’ Speaking Anxiety in EFL Classroom: A Descriptive Case Study - Fadillah, Farah Dhina; Mobit, Mobit; Abbas, Totoh Tauhidin (Peneliti.net, 2024)
Students' problems with fear of speaking a foreign language are usually related to the atmosphere built in the classroom. The educator's performance usually dominates the atmosphere in the classroom. This research aims to explore teacher's attitudes toward students' speaking anxiety in the classroom and what a teacher does to help students overcome their anxiety. Qualitative was used as a research design. This research involves one teacher and four students in junior high school. This research used interviews and observation to collect the data according to the theory of Zukani, N. M. (2018). The data analysis is adapted from the thematic analysis by Braun & Clark (2006). The findings showed that teachers had a very positive attitude toward the phenomenon of students' speaking anxiety in EFL classrooms. This research can be applied to every teacher in overcoming student problems when students have problems in speaking such as being afraid to speak or worrying about being wrong. This can be used to increase the effectiveness of learning in the classroom and can make students play a more active role because of the reduced anxiety possessed by students.